PENGARUH KETEBALAN ELEKTRODA KERJA TiO2/GRAFIT TERHADAP EFISIENSI DYE SENSITIZED SOLAR CELLS (DSSC) - Nurhidayah Nurhidayah; Suwarni Suwarni; Sri Rahayu Alfitri Usna; Muhammad Ficky Afrianto; Faizar Farid (Komunikasi Fisika Indonesia, 2019)
The production of Dye Sensitized Solar Cells (DSSC) has been done. The transparent electrode is made by mixing of TiO2 and graphite 14% (TiO2:C14%). TiO2:C14% colloid is deposited on a conductive glass substrate Fluorine Doped Tin Oxide (FTO) by spin coating method at 500, 1000 and 1500 rpm during 50 second. Then, the layer is soaked of 24 hours in dye taken from the extract of rosella. SEM and XRD characterization are performed for looking properties of DSSC materials. The efficiency of DSSC is calculated by using the characteristic circuit IV curve. The highest efficiency value is obtained when the thickest active layer (0,9 mm) at 500 rpm, the resulting efficiency is 0,014%.